Интегративно-когнитивный подход к обучению иностранных студентов-медиков записи лекций по специальности - Хейлик, В. Д.; Хейлік, В. Д.; Kheylik, V. D. (ЗДМУ, 2013)
Рассмотрены некоторые факторы эффективности обучения иностранных студентов языку специальности, в частности, новый подход к формированию умений конспектирования лекций медико-биологического профиля. Розглянуто деякі чинники ефективності навчання іноземних студентів фаховій мові, зокрема, новий підхід до формування вмінь конспектування лекцій медико-біологічного профілю. The article is devoted to some aspects of the effectiveness of the language training for medical higher school foreign students. Special attention is given to a new technological approach in teaching foreign students to make notes of the medical and biological profi le lectures.
Інтегративно-когнітивний підхід до навчання іноземних студентів-медиків запису лекцій за фахом
Integrative and cognitive approach to teaching of foreign medical students to take down lectures on speciality
Keywords: метатема; когнитивные операции; средства компрессии; когнітивні операції; засоби компресії; metatheme; cognitive operations; means of compression